The Implementation of The Strategy in Issuance of Birth Certificates in The Islands Region of Selayar District - Sunasih Mulianingsih; As’Ad Asyahadi Ichsan; Engkus Engkus (Universitas Padjadjaran, 2022)
This research is motivated by the people of the Selayar Islands Regency who experience limited information about birth certificate documents at this time, which is due to limited human and material resources both in quantity and quality, as well as the geographical location in the form of islands. The main problem of this research is that the issuance of birth certificates is still not optimal. The purpose of this study was to describe the issuance strategy by the Department of Population and Civil Registration of the Selayar Islands Regency in accelerating the ownership of birth certificates. This study uses qualitative research methods with the object of research being the issuance of birth certificates. Data collection techniques: observation, interviews, and documentation. Data analysis consists of three activities carried out together, namely data selection, presenting data, and drawing conclusions. The results of this study reveal that the Strategy of the Department of Population and Civil Registration has been running but still has obstacles in its implementation. This is due to various factors that occur in the field so that the implementation of the strategy has not been maximized. The researcher recommends that to reach services in the archipelago, it is better to use online. This will certainly make it easier for the community and officers to provide services in an effort to accelerate birth certificate ownership in the archipelago.